Safety and efficacy of dabigatran versus warfarin in Asian patients with atrial fibrillation - Inche Mat, Liyana Najwa; Ooi, Qi Wen; Johari, Nurul Natasha Ashikin; Subramaniam, Rooban Raao; Wan Sulaiman, Wan Aliaa; Hoo, Fan Kee; Chia, Peck Kee; Basri, Hamidon (Faculty of Medicine and Health Science, Universiti Putra Malaysia, 2020)
Introduction: Nonvalvular atrial fibrillation is a common cause of cardioembolic stroke which accounts around 50% of all cardioembolic emboli. Oral anticoagulants remain the main choice of stroke prevention in patients with atrial fibrillation. Our study is aimed to determine the safety (absence or presence of bleeding events) and efficacy (absence or presence of ischemic stroke occurrence) of dabigatran versus warfarin for stroke prevention in patients with nonvalvular atrial fibrillation. Methods: A retrospective audit study was conducted based on past data obtained from Electronic Hospital Information System (EHIS) records in Serdang Hospital. Our sample was 150 patients with nonvalvular atrial fibrillation who were at risk of getting stroke and being prescribed with oral anticoagulants either warfarin or dabigatran from the year 2013 until 2019. Results: Our study showed that there was lesser occurrence of ischemic stroke in patients from dabigatran group (1.3%) as compared to those in warfarin group (2.7%). There were also almost 2 times lesser bleeding events in dabigatran group (6.7%) as compared to those in warfarin group (14.7%). The median of CHA2DS2-VASc Score in warfarin sampled patients (median=3+/-1) was lower than dabigatran sampled patients (median=4+/-1). Conclusion: Both warfarin and dabigatran are effective in preventing stroke for patients with nonvalvular atrial fibrillation. However, dabigatran is associated with lesser bleeding events with lower incidence of major bleeds compared to warfarin.